Building up polymer architectures on graphene oxide sheet surfaces through sequential atom transfer radical polymerization. Issue 11 (18th March 2014) - Peng, Kang‐Jen; Wang, Ke‐Hsuan; Hsu, Keh‐Ying; Liu, Ying‐Ling
ABSTRACT The reactivity between the active species of atom transfer radical addition and the unsaturated groups of graphene oxides (GOs) has been demonstrated in this work. The reaction and the sequential surface‐initiated atom transfer radical polymerization provide a convenient approach to anchor various polymer chains and to buildup various polymer architectures, such as linear polymer, V‐shape block polymer, multibonded polymer layer, and hierarchical brush‐on‐layer polymer, on GO sheet surfaces. The chemical structures and morphology of the polymer‐modified GOs have been characterized with Fourier transform infrared spectroscopy, Raman spectroscopy, X‐ray photoelectron spectroscopy, and atomic force microscopy. After organomodification, the GOs exhibit a good dispersion ability in organic solvent over 80 days, amphiphilic characteristics, and temperature‐responsive properties. Reduction of the GOs has been performed to result in graphene‐like materials showing certain extent of electron conductivities. An effective approach to synthesize GO/polymer hybrid materials possessing various polymer architectures and attractive properties has been developed. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1588–1596